Penerapan PSAK No. 45 ( Revisi 2011) dalam Rangka Evaluasi Penyajian Laporan Keuangan yang Wajar pada Yayasan Taman Tunas Makassar - Saifan, Saifan; Marco, Trisisco Anthony (Universitas Patria Artha, 2018)
ABSTRACTThe purpose of study was compare compare the financial statements of Taman TunasFoundation as a non-profit organization and the financial statements of PSAK 45 as a standardfinancial report based on Ikantan Akuntan Indonesia (IAI). This study uses comparative method and data source obtained through observation, interview and foundation document in the formof financial statement. Based on this study, it can be seen that Taman Tunas Foundation has notfully applied PSAK 45 in its financial report. This is because the Taman Tunas Foundation stilluses the financial statements of the business and Taman Tunas Foundation has not made a cashflow statement so that the financial report of Taman Tunas Foundation has not beentransparent for the public.